Identity issues in groups - Polzer, Jeffrey T. (Research on managing groups and teams ;, 2003)
This fifth volume of Research on Managing Groups and Teams focuses on the relationship between identity issues and individual and group functioning. Identity issues encompass a wide range of phenomena involving the individual identities people bring to the groups they join, individuals' level of identification with particular groups they join, and the collective identities of specific groups or organizations. The authors in this volume take full advantage of the broad scope of identity-related phenomena, pushing our thinking about the interplay between identity and groups in new and exciting directions. In doing so, they make inroads into seemingly intractable practical problems with groups by understanding how these difficulties are rooted in the identities people strivve to create and maintian. This book should be of interest to social scientists from all domains who are interested in how identity issues influence the performance of individuals, groups and organizations.